The inhibitory effects of 7ND protein on osteoclast differentiation in apical periodontitis - Ji, Zhang-Zhang; Xu, Xiu-Min; Lu, Yu-Lin; Zhang, Run-Zhen; Zhang, Ying; Zou, Zhi-Hui; Xu, Qi (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundApical periodontitis (AP) is a highly prevalent inflammatory condition that affects the tissue surrounding the apex of a tooth root. 7ND protein, a mutant form of monocyte chemoattractant protein-1 (MCP-1), functions as a dominant negative inhibitor of MCP-1. Previous studies have shown that 7ND protein can suppress osteoclast differentiation in peripheral blood mononuclear cells, suggesting its potential to prevent inflammatory bone destruction. However, whether 7ND protein can inhibit AP-induced osteolysis remains unknown.MethodsTo investigate the effects of 7ND protein on osteoclast differentiation, we utilized RAW264.7 macrophage cells and an AP rat model. Western blotting analysis was employed to assess MCP-1 expression in RAW264.7 cells treated with 7ND protein. The impact of 7ND protein on osteoclast formation was evaluated both in vitro (using RAW264.7 cells) and in vivo (in AP rats). Additionally, X-ray imaging and micro-computed tomography were used to compare the lesion volume and area in the periapical regions of AP rats treated with 7ND protein versus those treated with PBS.ResultsWestern blotting analysis revealed that 7ND protein reduced MCP-1 expression in RAW264.7 macrophage cells without affecting their proliferation. Furthermore, 7ND protein significantly inhibited osteoclast formation in both RAW264.7 cells and AP rats. In AP rats treated with 7ND protein, X-ray imaging and micro-computed tomography demonstrated a significant decrease in lesion volume and area in the periapical regions compared to AP rats treated with PBS.ConclusionOur study demonstrates that 7ND protein has the potential to inhibit osteoclast differentiation and reduce bone loss associated with apical periodontitis. These findings suggest that 7ND protein may serve as a valuable therapeutic option for the treatment of AP-related osteolysis.